OPTIMIZATION OF COMPRESSION MOULDING PARAMETERS ON MECHANICAL PROPERTIES OF STAINLESS STEEL 316L - Ali, N.I.M.; Ali, M.A.M.; Salleh, M.S.; Subramonian, S.; Abdullah, M.I.H.C.; Yamaguchi, M. (Journal of Advanced Manufacturing Technology (JAMT), 2023)
Compression moulding is one of the forming processes for metal powder compounded with thermoplastic materials. The compounded materials feed directly into a heated mould and compressed to form a final product. Recently, compression moulding process has received more attention due to the cost effectiveness as compared to the expensive forming processes such as injection moulding and isostatic pressing. This article focuses on the optimization compression moulding parameters on mechanical properties such as ultimate tensile strength, elastic modulus and percentage of elongation. The parameters of compression moulding selected are mould temperature, weight of material and pre-heat time. Taguchi method with L4 orthogonal array was implemented in this experiment. After optimization, it was found that the weight of material is the most significant parameter on the ultimate tensile strength and elastic modulus. Meanwhile, preheat time is the most significant for percentage of elongation. It was shown that mould temperature was not significant parameter for this experiment. Thus, the weight of material and preheat time are the most important parameters affected the mechanical properties of stainless steel 316L.